Fatty acids suppress the steroidogenesis of the MA-10 mouse Leydig cell line by downregulating CYP11A1 and inhibiting late-stage autophagy - Chien Huang (Nature Portfolio, 2021)
Abstract Obese men have lower circulating testosterone than men with an optimal body mass index. Elevated fatty acids (FAs) caused by obesity have been reported to suppress the steroidogenesis of Leydig cells. Recent studies have demonstrated that autophagy regulates steroidogenesis in endocrine cells; however, few studies have investigated the molecular mechanisms of FA-impaired steroidogenesis. To study FA regulation in the steroidogenesis of Leydig cells, MA-10 cells were treated with an FA mixture and co-treated with 8-Br-cAMP to stimulate the steroidogenesis capacity. We showed that FAs led to cellular lipid accumulation and decreased steroidogenesis of MA-10 cells, and FA-suppressed steroidogenesis was largely recovered by P5 treatment but not by 22R-OHC treatment, suggesting the primary defect was the deficiency of CYP11A1. To examine the involvement of autophagy in the steroidogenesis of Leydig cells, we treated MA-10 cells with autophagy regulators, including rapamycin, bafilomycin, and chloroquine. Inhibition of late-stage autophagy including FA-upregulated Rubicon suppressed the steroidogenesis of MA-10 cells. More interestingly, Rubicon played a novel regulatory role in the steroidogenesis of MA-10 cells, independent of inhibitors of late-stage autophagy. Collectively, this study provides novel targets to investigate the interaction between FAs and steroidogenesis in steroidogenic cells.